Analysis of the Impact of the Covid-19 Pandemic on Sales Volume of Chicken Eggs in Konda District South Konawe Regency - Ahmad, Fadel; Bafadal, Azhar; Fyka, Samsul Alam (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2022)
The Covid-19 pandemic has impacted various economic sectors, one of which is the sale of purebred chicken eggs. This study aims to determine the impact of selling broiler eggs in Konda District, South Konawe Regency, during the Covid-19 pandemic. This research was conducted in March – November 2021. The population in this study was six chicken egg traders consisting of retailers and wholesalers. Using the census method, six people were obtained as research samples. The variables in this study are the respondent’s identity and sales of broiler eggs. The analysis used in this research is analyzed descriptively. This analysis compares deals of broiler eggs before and during the Covid-19 pandemic. The results showed that the impact of the Covid-19 pandemic caused a 23% decrease in the number of sales of broiler eggs at retail traders. Meanwhile, there is no decrease in sales of broiler eggs at wholesalers.